Feedback Trading: The Intraday Case of Retail Derivatives - Rainer Baule; Bart Frijns; Sebastian Schlie (Journal of Futures Markets, 2024)
We analyze retail order flow in terms of intraday feedback trading patterns. Using a unique data set of exchange trades and high-frequency quotes, we first provide evidence that retail investors actively and consciously respond to short-term intraday returns in a negative feedback, contrarian fashion. Second, we show that some retail investors also feedback trade on tick-by-tick returns. Third, we find that on average this behavior leads to significant losses on the day they open a position. These losses are primarily due to the bid-ask spread and to investors' timing inability, but not to market makers taking advantage of investors.
Keywords: 330; feedback trading; intraday; investor returns; issuer pricing strategies; retail derivatives; retail investors; warrants